Manajemen agresi pasien di unit perawatan jiwa: A literature review - Daisiu, Casey Petry; Kamaluddin, Ridlwan (Holistik Jurnal Kesehatan, 2025)
Background: Violent incidents in hospital settings, particularly in psychiatric units, create complex challenges for healthcare workers, patients, and hospital management. Aggression can range from verbal abuse to potentially harmful physical actions, and this phenomenon negatively impacts the well-being of healthcare workers and creates a care environment less conducive to recovery. Purpose: To analyze the most effective nursing management strategies for managing patients with aggressive behavior and provide evidence-based recommendations. Method: A systematic review was conducted using PRISMA, with a literature search conducted through PubMed, Science Direct, and Google Scholar. Seven relevant original research articles were analyzed during the selection process. Results: The most effective strategy was a holistic and integrated approach that did not rely on a single method. This included enhancing nurse competency through de-escalation and communication training, establishing strong organizational and system support, implementing structured risk assessments, and adopting a patient-centered care model. Conclusion: Comprehensive and adaptive aggression management is key to creating a safe and supportive care environment. Suggestion: Further research could quantitatively compare the effectiveness of different combinations of strategies and conduct more longitudinal studies to evaluate the long-term impact of organizational policy changes.   Keywords: Aggression Management; Patients; Psychiatric Nursing.   Pendahuluan: Insiden kekerasan di lingkungan rumah sakit terutama di unit psikiatri menciptakan tantangan yang kompleks bagi tenaga kesehatan, pasien, dan manajemen rumah sakit. Agresi dapat berupa kekerasan verbal hingga tindakan fisik yang membahayakan dan fenomena ini berdampak negatif pada kesejahteraan tenaga medis serta menciptakan lingkungan perawatan yang kurang kondusif bagi pemulihan. Tujuan: Untuk menganalisis strategi manajemen agresi pasien di unit perawatan jiwa.  Metode: Tinjauan sistematis mengacu pada PRISMA, dengan pencarian literatur melalui database PubMed, Science Direct, dan Google Scholar. Dari proses seleksi, tujuh artikel penelitian orisinal yang relevan dianalisis. Hasil: Strategi yang paling efektif adalah pendekatan holistik dan terintegrasi yang tidak bergantung pada metode tunggal. Peningkatan kompetensi perawat melalui pelatihan de-eskalasi dan komunikasi, adanya dukungan sistem dan organisasi yang kuat, implementasi penilaian risiko yang terstruktur, serta adopsi model perawatan yang berpusat pada pasien (patient-centered care). Simpulan: bahwa manajemen agresi yang komprehensif dan adaptif merupakan kunci untuk menciptakan lingkungan perawatan yang aman dan mendukung pemulihan. Saran: Penelitian selanjutnya disarankan untuk membandingkan efektivitas kombinasi strategi yang berbeda secara kuantitatif dan melakukan lebih banyak studi longitudinal untuk mengevaluasi dampak jangka panjang dari perubahan kebijakan organisasi.   Kata Kunci: Keperawatan Jiwa; Manajemen Agresi; Pasien.